1991
DOI: 10.1007/bf00201837
|View full text |Cite
|
Sign up to set email alerts
|

Some Mexican glucose-6-phosphate dehydrogenase variants revisited

Abstract: Glucose-6-phosphate dehydrogenase (G6PD) deficiency appears to be fairly common in Mexico. We have now examined the DNA of three previously reported electrophoretically fast Mexican G6PD variants, -G6PD Distrito Federal, G6PD Tepic, and G6PD Castilla. All three of these variants, believed on the basis of biochemical characterization and population origin to be unique, have the G----A transition at nucleotide 202 and the A----G transition at nucleotide 376, mutations that we now recognize to be characteristic o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
12
0

Year Published

1991
1991
2006
2006

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 11 publications
1
12
0
Order By: Relevance
“…As has been noted in previous studies [1,12,13,18], considerable differences in biochemical characteris tics were reported in variants that have now proved to be identical. As shown in table 1, the major differ ences between G6PD Jammu and G6PD Viangchan were in the utilization of 2-deoxy glucose-6-phosphate.…”
Section: Discussionsupporting
confidence: 47%
See 2 more Smart Citations
“…As has been noted in previous studies [1,12,13,18], considerable differences in biochemical characteris tics were reported in variants that have now proved to be identical. As shown in table 1, the major differ ences between G6PD Jammu and G6PD Viangchan were in the utilization of 2-deoxy glucose-6-phosphate.…”
Section: Discussionsupporting
confidence: 47%
“…Ex amination of the original data on G6PD Jammu also showed a pH optimum of 9.5, but since all points fell within the broad normal range the pH-activity curve had been designated as normal. Thus we sec that, as in an earlier study [12], biochemically dissimilar vari ants that prove to have the same mutation may seem much more similar when they are recharacterized.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…G6PD has been an extraordinarily important enzyme in biomedical research for two primary reasons. One reason is that deficiency of G6PD, formerly called favism or primaquine sensitivity, is probably the most common hereditary enzymatic abnormality in humans (De Flora, 1981;Beutler et al, 1991a). Indeed, it has been estimated (Beutler, 1991) that over 200 million people worldwide manifest some form of deficiency of this cytosolic enzyme, ranging from mild, nonsymptomatic reductions of activity in erythrocytes to severe deficiency associated with chronic hemolytic anemia and environmentally (food, drug) induced hemolytic crises (reviewed by Yoshida and Beutler, 1983;Beutler, 1990Beutler, , 1991.…”
mentioning
confidence: 97%
“…To date a total of 18 different G6PD variants have been observed in Mexico (Arámbula et al 2000;Arámbula 2002;Beutler et al 1991b;Beutler et al 1992;Lisker et al 1981;Medina et al 1995;Medina et al 1997;Vaca et al 2002;Vaca et al 2003) and 3 of them (both G6PD A -variants along with G6PD Santamaria variant) account for more than 80% of the overall prevalence of G6PD deficiency in Mexico (Arámbula 2002;Lisker 1981;Vaca et al 2002).This pattern of common G6PD variants is similar to that seen in other parts of the Americas such as Costa Rica (Beutler et al 1991c), Cuba (Rovira et al 1994), and Brazil (Hamel 2002;Weimer 1998). …”
mentioning
confidence: 99%